OTP based Door Lock using Arduino and SIM800L - G., Divya; Caffiyar, Mohamed Yousuff; Z., Mohammed Zabeer; K., Nehru Nandha; R., Abdul Rehaman; M., Kushalraj (IRO Journal on Sustainable Wireless Systems, 2024)
Nowadays, people prioritize security above all else, making it a more important concern in their lives. The proposed work aims to replicate the extensive literature research on OTP-based door locks, which are crucial for residential, commercial, and auto security because of ever increasing risk of theft. The existing methods include various kinds of door lock security systems, such as traditional security systems that transmit signals through alarms. Some door lock security systems are based on GSM, GPS, and biometrics like face recognition, iris scanning, RFID, smart cards, and passwords. Every system has benefits and drawbacks of its own. Overcoming the limitations of authentication mechanisms like mechanical and digital door locks is the reason why access control systems based on OTP are preferred. The user does not require the administrator’s help to access the door if they are familiar with the proposed method and have the registered mobile number and OTP. The OTP is generated and sent to user’s mobile number whenever the user accesses the door.
Keywords: Door Lock Security; GSM; SMS; Sensor; LCD Display; Password